Characterization of Solvent-Fractionated Mustard Oil by High Performance Liquid Chromatography (Progressive Agriculture, 2013)
Mustard oil (MO) was fractionated at low temperature with acetone. The liquid fraction obtained at -24°C, showed higher levels of oleic (24.7%) and linoleic (22.0%) acids, and lower level of erucic acid (24.5%) compared to other fractions. The lowest temperature (-24°C) was most effective for lowering the level of erucic acid through crystallization of triacylglycerol (TAG) molecules. One purpose of this study was to obtain erucic acid reduced fractions because erucic acid has undesirable effect on human health. The result suggested that erucic acid could be separates as solid fraction thereby better reduction of erucic acid would be possible at lower temperature.DOI: http://dx.doi.org/10.3329/pa.v19i1.17364 Progress. Agric. 19(1): 135 - 141, 2008